Civil Society dan al-Madīnah al-Fāḍilah: Konvergensi dan Ketegangan antara Otonomi Warga dan Politik Kebajikan - Ahmad Nur Fauzi; Hadi Kharisman (Paradigma: Jurnal Kalam dan Filsafat, 2025)
This article critically examines the relationship between modern civil society and al-Fārābī’s theory of al-madīnah al-fāḍilah. It employs philosophical library research and comparative conceptual analysis of civil society, political virtue, citizenship, leadership, and the common good. The study finds an ethical convergence between the two frameworks in their emphasis on social cooperation, civic education, public morality, and common welfare. Nevertheless, a structural tension persists between the autonomy, pluralism, and distributed authority of modern civil society and the teleological and hierarchical leadership of al-Fārābī’s virtuous city. Therefore, al-madīnah al-fāḍilah cannot be regarded as an early institutional model of civil society. Its contemporary relevance lies instead in providing an ethical critique of civil society when it becomes excessively procedural, individualistic, and detached from moral purposes. Al-Fārābī’s political philosophy can thus contribute to reconstructing civil society as an arena of civic virtue oriented toward the common good.